The Use of Ensembles in Space Weather Forecasting - J. A. Guerra; S. A. Murray; E. Doornbos (Space Weather)
Abstract In order to advance the use of ensembles in forecasting space weather events, the workshop Ensemble Forecasts in Space Weather: Science and Operations took place at the Lorentz Center in Leiden, The Netherlands, on 2–6 September 2019. The aim of this workshop was to bring together space weather scientists from academic institutions and operational centers and experts in ensemble techniques in terrestrial weather forecasting. Ensembles are currently used across all the subfields of space weather; however, there seems to be no community‐wide consensus about how to best utilize them. Therefore, the Testing, Understanding, and Leveraging Ensemble Predictions for Space Weather (TULEPS) working group was created to provide a starting point for the space weather community to the use of ensemble techniques.